Underestimated diversity: Integrative taxonomy of Mesenchytraeus (Enchytraeidae, Clitellata) from Changbai Mountain, China - Juanjuan Chen; Rüdiger M. Schmelz; Junqian Zhang; Zhicai Xie (Zoologica Scripta, 2024)
The holarctic genus Mesenchytraeus is one of the species‐rich genera in the family Enchytraeidae. Changbai Mountain supports high diversity of Mesenchytraeus species, making it an ideal area to explore species boundaries. We explored species boundaries of Mesenchytraeus using an integrative approach. Morphological taxonomy recognized 10 species in this region, five of them new to science. In contrast, molecular species delimitation analyses showed that there are at least 16 species, 11 of them new to science. Clear genetic gaps were observed among species with high interspecific distances (10%–21.2%) and low intraspecific distances (0.2%–6.7%) based on uncorrected p‐distance of the COI gene. Morphological species complex M. spermatoglomeratus consists of three species, M. spermatoglomeratus Zhang, Lu & Xie, 2018 sensu stricto, M. rijina sp. n., and M. manchu sp. n. The M. duodiverticulus complex consists of M. duodiverticulus sp. n. and M. similiduodiverticulus sp. n. The M. monodiverticulus complex consists of M. monodiverticulus Shen, Chen & Xie, 2012 sensu stricto, M. ngulen sp. n., M. zhenggulen sp. n., and M. fokulen sp. n. Further new species, distinguishable with morphological as well as molecular methods, are M. similigigachaetus sp. n., M. parvidiverticulus sp. n., M. digitalisdiverticulus sp. n., and M. infradiverticulus sp. n. Finally, we inferred the morphogenetic processes of spermathecae and sperm bundles, and filtrated some morphological characters which are useful to identify species. As the first attempt in this genus, our study provides an opportunity to discuss the currently used taxonomic criteria and acquire new ideas for the taxonomy of enchytraeids.